Exploring the potential anti-apoptotic effects of traditional Chinese medicine in intervertebral disc degeneration: mechanisms and therapeutic prospects - Zhang, Kuaixiang; Wan, Lei; Khan, Malik Ihsan Ullah; Pu, Feifei; Liu, Man; Zhao, Zhiqiang; Li, Jitian (Frontiers in Physiology, 2025)
Intervertebral disc degeneration (IDD) stands as one of the primary culprits behind low back pain and disability, imposing substantial burdens on individual health, families, and societal wellbeing. The multifactorial etiology and complex pathology of IDD pose significant challenges, with molecular mechanisms still not fully elucidated. A key aspect of the pathogenesis of IDD involves programmed cell death, specifically apoptosis, which exacerbates the condition by fostering the apoptosis of intervertebral disc (IVD) cells and accelerating the degradation of the extracellular matrix (ECM). Conversely, inhibiting apoptosis signalling pathways has emerged as a promising therapeutic strategy for IDD. Recent research has highlighted the potential of traditional Chinese medicine (TCM) to alleviate IDD at the genetic level by modulating apoptotic pathways. This review integrates the intricate mechanisms of IDD-induced cell apoptosis, the relevant targets implicated in IVD cell apoptosis, and the latest advancements in TCM-based treatments, drawing from a comprehensive analysis of literature sourced from the PubMed, China National Knowledge Infrastructure (CNKI), and Web of Science databases. This study aims to offer fresh perspectives and innovative concepts for pharmacological interventions and to serve as a valuable reference for ongoing and future research endeavors. As the field of antiapoptotic research progresses, there is increasing urgency to identify safe, effective, and economically viable compounds from the vast array of natural resources, including plants and animals, to support the prevention and management of IDD. This approach not only aligns with the principles of sustainable development but also holds the promise of enriching the therapeutic armamentarium against IDD.